Problematika Moralitas Seksual Postmodern menurut Perspektif 1 Korintus 6:12-20 - Alfons Tampenawas (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
This article uses a literature study method that discusses the problems ofpostmodern sexual morality from the perspective of 1 Cor. 6:12-20. The corruption of secual morality from the life of the Corinthians, which is amoral and arbitrary, still occurs until this postmodern era, such as prostitution, inces (sexual relations with siblings), and homosexuality. This article aims to see the extent to which morality is a reference or value in people’s lives in the postmodern era. Hermeneutics becomes a method of study ini 1 Coronthians 6:12-20. The choice of the text 1 Cor. 6:12-20,because the text discusses in principle how sexual morality is biblical. Theresults of this research indicate that morality is a reference or value of life forsociety, including believes, so this research is expected to become a foundation for a new morality in the postmodern era.